The prevalence of anxiety symptoms/disorders in cancer patients: a meta-analysis - Amiri, Sohrab (Frontiers in Psychiatry, 2024)
Cancer can have negative effects on mental health. The aim of this study was to investigate the prevalence of anxiety symptoms/disorders in cancer patients' worldwide using meta-analysis.The study population was cancer patients who had cancer at the time of the study. The outcome studied in this study was anxiety symptoms/disorders. PubMed and Scopus were searched based on the syntax of keywords, this search was limited to articles published in English until September 2021.For this meta-analysis, data on the prevalence of anxiety were first extracted for each of the eligible studies. The random-effects method was used for the pool of all studies. Subgroup analysis was performed based on sex, anxiety disorders, cancer site, and continents. Heterogeneity in the studies was also assessed.After evaluating and screening the studies, eighty-four studies were included in the meta-analysis. Prevalence of anxiety symptoms/disorders in cancer patients showed that this prevalence is 23% (I 2 =99.59) in the 95% confidence interval between 22-25%. This prevalence was 20% (I 2 =96.06%) in the 95% confidence interval between 15-24% in men and this prevalence is 31% (I 2 =99.72%) in the 95% confidence interval between 28-34% in women. The highest prevalence of anxiety was in patients with ovarian, breast, and lung cancers.It showed a high prevalence of anxiety symptoms/disorders in cancer patients, in addition to therapeutic interventions for cancer, the necessary interventions should be made on the anxiety of these patients.Methodological limitation was the heterogeneity between the studies included in the meta-analysis. Some types of cancer sites could not be studied because the number of studies was small or the site of cancer was not identified.